2018
DOI: 10.1016/j.molmed.2018.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Adult Human Hippocampal Neurogenesis: Controversy and Evidence

Abstract: The hippocampus has been described as one of the few sites in the mammalian brain capable of generating new cells continuously throughout life. Two recent studies that report contradicting findings on adult human hippocampal neurogenesis, however, reminds us of the caveats and challenges of studying this phenomenon in postmortem tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 10 publications
0
29
0
1
Order By: Relevance
“…This led to great controversy, and very recent publications question or contradict these postmortem findings [38,39,40], although there is a possibility that neurogenesis in the adult hippocampus can be deregulated by neurological diseases, such as epilepsy or behavioral disorders [41], which would explain the current divergent opinions about the persistence of adult neurogenesis in man throughout life.…”
Section: Discussionmentioning
confidence: 99%
“…This led to great controversy, and very recent publications question or contradict these postmortem findings [38,39,40], although there is a possibility that neurogenesis in the adult hippocampus can be deregulated by neurological diseases, such as epilepsy or behavioral disorders [41], which would explain the current divergent opinions about the persistence of adult neurogenesis in man throughout life.…”
Section: Discussionmentioning
confidence: 99%
“…Cause versus effect in disease processes still need to be determined, and in light of the most recent studies calling into question, the presence of adult neurogenesis in humans, the association with adult neurogenesis and human disease needs to be re‐evaluated. Lee and Thuret () suggest researchers should investigate the gene expression changes in the human brain at the transcriptome level. It is possible (although difficult) to carry out single‐cell RNA‐sequencing analysis on post‐mortem brain tissues; such an approach could provide better molecular markers for human hippocampal neurogenesis.…”
Section: Adult Neurogenesis In the Human Brainmentioning
confidence: 99%
“…Inconsistent reports over the maintenance of hippocampal neurogenesis over the lifespan in humans have brought about recent debate about its functional significance (reviewed by Lee & Thuret, ; Snyder, ). In a recent investigation of postmortem brain tissue obtained from 18 adults and 19 perinatal and postnatal samples (age range: 14 gestational weeks to 77 years), it was reported that no newborn neurons were found in the DG of adults and only a few isolated young neurons were observed in samples from young individuals (7–13 years of age).…”
Section: Adult Hippocampal Neurogenesismentioning
confidence: 99%